Failure criterion analysis and reliability assessment in process of cartridge ejection. (February 2019) - Yu, Xinshui; Yu, Tianxiang; Song, Lingkun; Song, Bifeng
Abstract: Case ejecting device is one of the most important devices of a tank, whose performance influences the working performance of a tank directly. This study focuses on the failure criteria analysis and reliability assessment of the projecting process of an ejector. Firstly, the failure mechanism of projecting process is studied and the condition of cartridge case can't be thrown out of the window occurs frequently. Secondly, the simulation model of projecting process is established by using the LMS Virtual Lab, then, it is validated by mathematical model. Then, the failure criterion is established by considering the trajectory of cartridge case's mass center and the size of window. The expression of up and down range of cartridge case is got. Finally, reliability is assessed based on the simulation model. The torque generated by torsional springs and the angle of collector are the two main factors which impact the performance of ejector, so the failure boundary and the relationship of the two factors are also calculated by this model. By using the assessment of reliability and failure boundary of main factors, the performance of projecting process of ejector can be improved in practice